Indiffusion of oxygen in germanium induced by pulsed laser melting. (December 2018) - Milazzo, R.; Linser, M.; Scarpa, D.; Carnera, A.; Andrighetto, A.; Napolitani, E.
Abstract: A systematic study of the indiffusion of oxygen in germanium induced by pulsed laser melting (PLM) is reported. In order to evidence the impact of the experimental parameters, different processing conditions have been compared, i.e. with or without pre-PLM etching of the Ge native oxide by H2 O or HF dip, Air or N2 -rich atmosphere, and single or multi-pulse PLM. Oxygen indiffusion is always observed with surface concentration above 1 × 10 19 cm −3 for all the processing conditions. Pre-PLM surface chemical treatments seem to have no significant influence in terms of the oxygen penetration, although HF allows lower surface roughening. On the contrary, a processing atmosphere with reduced oxygen concentration is more efficient in reducing the overall O indiffusion. The present experimental results are crucial in view of the implementation of the PLM technique for highly doped Ge as well as to design studies where contamination issue might be crucial.